Prevalence of depression and anxiety in people with inflammatory bowel disease and associated healthcare use: population-based cohort study - Irving, P; Barrett, K; Nijher, M; de Lusignan, S (BMJ Publishing Group, 2021)
Background Inflammatory bowel disease (IBD) has a significant impact on quality of life for many people. Objective To assess the prevalence of common mental health conditions in IBD and the combined impact of IBD and mental health conditions on healthcare use and time off work. Methods A UK population-based primary care database (Royal College of General Practitioners Research and Surveillance Centre) was used to identify adults with IBD (n=19 011) (Crohn’s disease (CD) or ulcerative colitis (UC)), and matched controls (n=76 044). Prevalences of anxiety, depressive episodes and depressive disorder recorded in primary care were assessed between 2016 and 2018. Outcomes comprised of rates of primary care visits, emergency secondary care visits, certificates for time off work, antidepressant and anxiolytic prescriptions. Findings Mental health conditions were more common in people with CD than controls: anxiety episodes (3.5% vs 3.0%; p=0.02), depressive episodes (5.7% vs 4.1%; p<0.001) and depressive disorder (17.5% vs 12.9%; p<0.001), and people with UC versus controls: depressive episodes (4.4% vs 3.6%; p<0.001) and depressive disorder (14.2% vs 12.4%; p<0.001). Healthcare utilisation rates were higher in people with IBD than controls (primary care visits incidence rate ratio 1.47 (95% CI 1.43 to 1.51); emergency secondary care visits 1.87 (1.79 to 1.95); fitness for work certificates 1.53 (1.44 to 1.62); antidepressant use 1.22 (1.13 to 1.32); anxiolytic use 1.20 (1.01 to 1.41)). In people with IBD, mental health conditions were associated with additional increases in healthcare use and time off work. Conclusion Depression and anxiety are more common in people with IBD than matched controls. Healthcare utilisation and prescribing of psychotropic medications are also higher in people with IBD. Mental health conditions in people with IBD are associated with additional healthcare use and time off work. Clinical implications Evidence-based mental health support programmes, including psychological treatments, are needed for people with IBD.